2022
DOI: 10.3390/met12081235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CaO, Al2O3 and MgO on Kinetics of Lead-Rich Slag Reduction

Abstract: Lead-rich slag as a green feedstock can be used in a blast furnace or smelting reduction furnace to produce lead metal. It is desirable to understand the reduction mechanisms of lead-rich slag to optimize the reduction operations. The volume of CO/CO2 gases was continuously measured in the experiments to determine the reduction degree of lead-rich slag by carbon. The effects of CaO, Al2O3 and MgO on reaction kinetics of lead-rich slag with carbon were investigated in the temperature range 1073 to 1473 K. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The minimum liquidus temperature in the olivine primary phase field was found to be 1117 • C. This means that a fully liquid slag can be obtained at temperatures above 1117 • C with optimum flux additions. Mukhopadhyay et al [21] studied the phase relations in CaFeSiO 4 -Fe 2 SiO 4 and found a miscibility gap below approximately 1041 • C. the sinter plant-blast furnace process due to its high thermal efficiency, less feed preparation, and efficient SO2 utilization [16]. Although oxygen pressure leaching has been developed for producing zinc in recent years, pyrometallurgy is still utilized to extract zinc from lead and zinc mixed concentrate [17].…”
Section: Phase Equilibrium Studies At Iron Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum liquidus temperature in the olivine primary phase field was found to be 1117 • C. This means that a fully liquid slag can be obtained at temperatures above 1117 • C with optimum flux additions. Mukhopadhyay et al [21] studied the phase relations in CaFeSiO 4 -Fe 2 SiO 4 and found a miscibility gap below approximately 1041 • C. the sinter plant-blast furnace process due to its high thermal efficiency, less feed preparation, and efficient SO2 utilization [16]. Although oxygen pressure leaching has been developed for producing zinc in recent years, pyrometallurgy is still utilized to extract zinc from lead and zinc mixed concentrate [17].…”
Section: Phase Equilibrium Studies At Iron Saturationmentioning
confidence: 99%
“…Similar to the smelting technology used in copper production, flash smelting [14] and bath smelting [15] technologies are the main oxidation methods employed for lead concentrates. Bath technology has replaced the sinter plant-blast furnace process due to its high thermal efficiency, less feed preparation, and efficient SO 2 utilization [16]. Although oxygen pressure leaching has been developed for producing zinc in recent years, pyrometallurgy is still utilized to extract zinc from lead and zinc mixed concentrate [17].…”
Section: Introductionmentioning
confidence: 99%